Zombies in the academy : living death in higher education - Whelan, Andrew; Walker, Ruth, 1969-; Moore, Christopher (Christopher L.) (Intellect, 2013)
Zombies in the Academy taps into the current popular fascination with zombies and brings together scholars from a range of fields, including cultural and communications studies, sociology, film studies, and education, to give a critical account of the political, cultural, and pedagogical state of the university through the metaphor of zombiedom. The contributions to this volume argue that the increasing corporatization of the academy - an environment emphasizing publication, narrow research, and a vulnerable tenure system - is creating a crisis in higher education best understood through the l.